Le renouvellement de la pensée économique durant la crise des années 1930. Le découplage théorie économique / politique économique - Jean-François Ponsot; Michel Rocca (Revue de la Régulation)
The article is related to the evolution of the economic thought when it is confronted with a severe economic and financial crisis. The article studies the special case of the crisis of the 1930s. We reject the common kuhnian view according to which the crisis would infer inevitably new theoretical advances which would contribute to the spontaneous emergence of a new “paradigm” in economics. And so on would influence the implementation of innovative (heterodox) economic policies set up by policy makers to go out of the crisis. Certainly the crisis of the 1930s favoured the emergence of new theoretical approaches and put on rails the keynesian revolution. But their emergence is previous to the crisis. Moreover the theoretical renewal has been complex and little comparable to a continuous process. Policy makers at the origin of innovative policies to exit from the crisis (for example Roosevelt and the New Deal), were more guided by the pragmatism and the necessity of bringing concrete answers to the crisis that by the prescriptions of the new economic theory in gestation. The article concludes that the crisis implies a decoupling between economic theory and economic policy, leaning on the concomitance of three dynamics: the renewal of the dominant economic thought, the emergence of a heterodox theory, and the setting up of innovative public policies by pragmatic policy makers. The new “paradigm”, if it exists, is only the result of these three dynamics.